Relationships between consumption of alcoholic beverages and healthy foods: the French supermarket cohort of 196, 000 subjects. (February 2015) - Hansel, Boris; Roussel, Ronan; Diguet, Vincent; Deplaude, Amandine; Chapman, M John; Bruckert, Eric
Aims: Moderate alcohol consumption is associated with reduced risk of cardiovascular disease. Related dietary habits and lifestyle may bias assessment of the relationship between alcohol intake and health status. We examined the relationship between key features relating to the consumption of alcoholic beverages and individual profiles of objective food purchases. Methods and results: Data were collected on regular clients of a large supermarket chain implanted across France ( n  = 196, 604). Food items purchased were classified into three categories: (1) healthy foods; (2) unhealthy foods; and (3) others. Wine consumers favoured purchase of healthy foods more often than others, whereas the lowest level of healthy food purchasers was associated with consumption of beer and aniseed-based beverages. Bordeaux wine purchasers spent less in their average budget than the whole population for nine out of the 11 unhealthy food categories. Conversely, the budget was markedly higher in non-alcohol purchasers as compared to the whole population for seven out of the 11 unhealthy foods. The ratio of the budget for healthy to that for unhealthy foods was also distinct between the groups, being highest for wine and lowest for beer. In the subgroup of non-alcohol consumers, this ratio was intermediate but significantly lower relative to values in the five subcategories of wine purchasers. Conclusions: Marked differences in the profile of the purchase of healthy versus unhealthy food products as a function of the subcategory of alcoholic beverage consumed were documented, revealing a critical unidentified confounding feature in analyses of the potential relationship between alcohol consumption and protection against cardiovascular disease.